High Antioxidant Activity of Pucuk Merah (Syzygium oleina) Leaf and Zinnia (Zinnia elegans) Flower Extracts - Purnomo, Tantyo Ardy Bintoro; Yuliati, Leny (Ma Chung Research Center for Photosynthetic Pigments, 2020)
A study on the antioxidant activity of natural sources is very crucial to explore their benefits, especially for food, medicine, as well as cosmetic applications. In this work, the antioxidant activities of pucuk merah (Syzygium oleina) leaves and zinnia (Zinnia elegans) flower were examined. Pucuk merah leaves and zinnia flowers were extracted using an acidic ethanol solvent by a simple maceration method for 24 hours. The color of the obtained pucuk merah leaf extract was red, while the zinnia flower extract was yellowish-brown. UV-visible spectrophotometer showed that the pucuk merah leaf extract has anthocyanin as the main part and chlorophyll as the minor part. On the other hand, zinnia flower extract contained carotenoid as the main part, as well as small parts of anthocyanin and chlorophyll. The antioxidant activity test was carried out by using 2-2-diphenyl-1-picrylhydrazyl (DPPH) as the antioxidant assay. It was revealed that the inhibitory concentration at 50% (IC50) values of the pucuk merah leaf and zinnia flower extracts were 25.83 and 20.16 mg/L, respectively, while the antioxidant activity index (AAI) of the pucuk merah leaf and zinnia flower extracts were 1.55 and 1.98, respectively. These results showed that both pucuk merah leaf and zinnia flower extracts have strong antioxidant activity, and thus very potential to be used as great antioxidants.